-8 (x + 2) = 2 (8x + 40) x = -4 | 10 (x + 9) = -2 (10x - 150) x = 7 |
10 (3x - 4) = 8 (-8x - 5) x = 0 | 8 (6x - 1) = (7x - 172) x = -4 |
3 (9x - 122) = 7 (-7x + 2) x = 5 | 4 (7x - 34) = -5 (7x + 2) x = 2 |
-(-2x - 361) = 7 (9x + 8) x = 5 | 5 (7x - 2) = 4 (8x + 5) x = 10 |
3 (4x - 4) = 4 (10x - 10) x = 1 | -9 (4x + 4) = (4x + 244) x = -7 |
(7x + 35) = 7 (4x + 5) x = 0 | 9 (2x + 2) = 6 (7x - 5) x = 2 |
6 (8x + 2) = (-5x + 224) x = 4 | 6 (4x + 15) = 10 (3x + 3) x = 10 |
7 (3x + 4) = 7 (8x - 6) x = 2 | 10 (10x + 1) = 2 (7x + 5) x = 0 |
-(6x - 387) = 9 (8x - 9) x = 6 | -3 (5x + 6) = -6 (3x + 1) x = 4 |
6 (-3x + 3) = -6 (8x - 8) x = 1 | -(2x - 90) = 6 (4x + 2) x = 3 |